2021
DOI: 10.3389/fcell.2021.630248
|View full text |Cite
|
Sign up to set email alerts
|

A Balanced Act: The Effects of GH–GHR–IGF1 Axis on Mitochondrial Function

Abstract: Mitochondrial function is multifaceted in response to cellular energy homeostasis and metabolism, with the generation of adenosine triphosphate (ATP) through the oxidative phosphorylation (OXPHOS) being one of their main functions. Selective elimination of mitochondria by mitophagy, in conjunction with mitochondrial biogenesis, regulates mitochondrial function that is required to meet metabolic demand or stress response. Growth hormone (GH) binds to the GH receptor (GHR) and induces the JAK2/STAT5 pathway to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 146 publications
(182 reference statements)
2
19
0
Order By: Relevance
“…In mammals, IGF1 is an important cytokine that stimulates the host's immune response, including antibody production, lymphocyte proliferation, phagocytosis, and natural killer cell activity (Auernhammer and Strasburger, 1995 ; Jeay et al, 2002 ; Yada, 2007 ). GH combines with GHR to activate the synthesis of IGF1 by the phosphorylation of JAK2/STAT5 (Hu et al, 2021 ). It has been proven that GH, directly or indirectly through the IGF1, influences both cellular immunity and humoral immunity (Hakuno and Takahashi, 2018 ; Szalecki et al, 2018 ).…”
Section: Growth Hormone and The Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, IGF1 is an important cytokine that stimulates the host's immune response, including antibody production, lymphocyte proliferation, phagocytosis, and natural killer cell activity (Auernhammer and Strasburger, 1995 ; Jeay et al, 2002 ; Yada, 2007 ). GH combines with GHR to activate the synthesis of IGF1 by the phosphorylation of JAK2/STAT5 (Hu et al, 2021 ). It has been proven that GH, directly or indirectly through the IGF1, influences both cellular immunity and humoral immunity (Hakuno and Takahashi, 2018 ; Szalecki et al, 2018 ).…”
Section: Growth Hormone and The Immune Systemmentioning
confidence: 99%
“…In poultry, PRL and GH are related to growth, development, and reproduction (Nie et al, 2005 ; Qin et al, 2013 ; Wilkanowska et al, 2014 ). However, some studies have shown that after chicken infected with some pathogens, such as Eimeria tenella ( E. tenella ) (Chadwick et al, 1985 ; Davison et al, 1985 ), Histomonas meleagridis (Chadwick et al, 1980 ), infectious bronchitis virus (IBV) (Nii et al, 2015 ), Newcastle disease virus (NDV) (Rehman et al, 2020 ), infectious bursal disease virus (IBDV) (He et al, 2018 ; Yu et al, 2019 ), Marek's disease virus (MDV) (Liu et al, 2001 ) and avian leukosis virus (ALV) (Carter and Smith, 1983 , 1984 ; Dai et al, 2019 ; Mo et al, 2021 , 2022 ), it is found that the hormone levels are changed, and they are involved in regulating the body immune response (Allen et al, 1997 ; Breuel et al, 2004 ; Hartwell et al, 2014 ; Yu et al, 2020 ; Hu et al, 2021 ). These evidences suggest that hormones are involved in the immune responses under specific conditions, which present an often-overlooked challenge to the conventional idea that hormone merely as endocrine hormone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth hormone (GH), a peptide hormone regulated by the hypothalamus and secreted by the pituitary gland, binds to cell surface growth hormone receptors to regulate metabolic processes and growth and development ( Hu et al, 2021 ). Growth hormone receptor (GHR), a member of the type I cytokine receptor family, is the key receptor transmembrane protein in the GH–GHR axis.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy, functional mitochondria could serve an important role in muscle regeneration after muscle damage (Sin et al, 2016), and previous reports demonstrate that hormonal stimuli influence mitochondrial dynamics and mitophagy (Guo et al, 2012;Hu et al, 2021;Lu et al, 2020;Pronsato et al, 2020). However, no prior research has investigated the effect of the sex-specific RE-induced hormonal changes (e.g., testosterone) on the mitochondrial response after muscle damage.…”
Section: Introductionmentioning
confidence: 99%